2005
DOI: 10.1080/08993400500224419
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predictors of success for an objects-first CS1

Abstract: The paper reports on an examination of predictors of success for an objects-first course. The predictors considered included prior programming experience, mathematical ability, academic and psychological variables, gender, and measures of student effort. Cognitive and academic factors such as SAT scores and critical thinking ability offered little predictive value when compared to the other predictors of success. Student effort and comfort level were found to be the strongest predictors of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 26 publications
6
73
1
Order By: Relevance
“…A t-test revealed significant differences in the performance those students who had prior programming experience prior to enrolling on the course (n = 15, M = 71.76, SD = 10.47) and those students who did not (n = 24, M = 64.34, SD = 10.70), (t(37) = 2.12, p < .05). These findings are consistent with previous research such as [25], but contradict research such as [2,18]. Further analysis showed more interesting relations between prior experience and performance; however none of the following measures were significant, (p > .05).…”
Section: Previous Programming Experiencesupporting
confidence: 77%
See 2 more Smart Citations
“…A t-test revealed significant differences in the performance those students who had prior programming experience prior to enrolling on the course (n = 15, M = 71.76, SD = 10.47) and those students who did not (n = 24, M = 64.34, SD = 10.70), (t(37) = 2.12, p < .05). These findings are consistent with previous research such as [25], but contradict research such as [2,18]. Further analysis showed more interesting relations between prior experience and performance; however none of the following measures were significant, (p > .05).…”
Section: Previous Programming Experiencesupporting
confidence: 77%
“…To date only 3 studies [8,11,18] have explored relationships between attributions and performance. Significant (p < .05), but weak, correlations were found between performance and attributions of success to task difficulty (r = -.10), and attributions to effort (r = .07).…”
Section: Attributions Of Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the area of introductory object-oriented programming there has been research trying to establish general factors to predict success or failure of particular students. Especially the work of Phil Venture [27] focuses on a systematic evaluation of hypothesis related to the factors for success of an introductory programming course using an objects-first approach [14]. The results are documented in [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rountree et al (2002) found that the grade a student expected to achieve in an introductory module was the most important indicator of performance. Ventura (2005) examined predictors of a graphical design-centric objects-first Java course and found that student effort (as measured by the number of hours spent using the labs) and comfort level were the strongest (positive) predictors of success. Newsted (1975) in a study of introductory Fortran, students found that two of the most important predictors of performance were perceived ability and time spent working on the course and working with other students.…”
Section: Review Of Literaturementioning
confidence: 99%